Pengembangan Sistem Informasi Terintegrasi Pada Pelaporan Rekam Medis, Retribusi Daerah dan Kinerja Pegawai di UPTD Pusat Kesehatan Hewan Kota Pangkalpinang - Riki Afriansyah; Muhammad Setya Pratama (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Data integration is necessary to facilitate the processing of reporting but there are still many local government agencies that have not implemented integrated information systems so that in the management of reports is done repeatedly and takes a very long time. Medical record data relates to regional retribution data and employee performance data; therefore, it is necessary that information systems integrate the data so that reporting processing is easier. Data relation between medical records and regional retribution services, there are as many as twelve types of services and relation of medical record data with employee performance, namely on reporting the implementation of activities carried out by veterinary medical officers on animal examination and treatment. In the development of information systems using prototype methods to create the system entry interaction and feedback from the system user to the information system developed to suit the user's needs. The results of evaluation with technology acceptance models obtained above 80% of users feel the ease, benefit, and acceptance of this information system according to the needs of the user.